Role of rigid bronchoscopy in massive haemoptysis - Ng, Teck Han; How, Soon Hin; Kuan, Yeh Chunn; Raja Lope Ahmad, Raja Ahmad Al'konee; Abdul Rani, Mohammed Fauzi (University Malaya, 2010)
Massive haemoptysis can occur in lung abscess. Massive haemoptysis itself may be life threatening due to asphyxiation or respiratory failure secondary to acute large airway obstruction by blood clots. Prompt removal of the obstructing blood clots save life. We describe a case of lung abscess causing massive haemoptysis resulting in acute airway obstruction which required rigid bronchoscopy to remove the huge blood clot.